Plataformas digitales y riesgos de conglomerado: desafíos para las autoridades de competencia en Iberoamérica en el análisis de operaciones de concentración - Von Chrismar Medina, Andrea (2021)
This article explores the subject of merger operations, specifically, on digital platforms. Thus, it analyzes the possible risks of these and the challenges that antitrust agencies must face when analyzing them. In this way, the authors highlight various characteristics of this market such as its dynamism and unpredictability, which allows it to adapt to the increase in demand, and the important role of user data in merger operations.To fulfill this objective, the article begins with a theoretical approach, providing definitions of key concepts for the understanding of merger operations on digital platforms. Nevertheless, it also offers a practical analysis, by exploring how these types of mergers have been taking place in reality, through recent cases of judgements relevance.